مفهوما "المدينة" و "القرية": دراسة ديكرونية سوسيو- لسانية - أ.م.د. سعيد ياسين جواد (Thi Qar Arts Journal, 2021)
The concepts “city” and “village”: a diachronic socio-linguistic sturdy The research deals with the vocabulary of the city and the village, tracing the historical origin of both in the Arabic language and in many languages ​​from different linguistic trees, as the research confirms that cities arose as a residence for the occupying armies, and therefore they arose in fortified places, sometimes high, for fear of attacks by the local population. The research also tries to prove that the terms city and village change locations and have almost the same meaning in Semitic languages, and in Arabic in particular, and the phenomenon extends to other languages ​​in the Indo-European tree. The research proposes the hypothesis that the word city in the ancient Greek polis is a loan translation (calque) of the same word in Akkadian, meaning the place of judgment. It also proposes the hypothesis that the synonym in Greek astoi is also taken by a loan translation from the same word in Sumerian, i.e. stable or settled.